Contribuição ao estudo de propriedades geotécnicas de um depósito de argila mole da baixada fluminense - Ortigão, José Alberto Ramalho (1975)
This paper, as a contribuition to the study of geotechnical properties to the natural soft clay deposits, presents and discusses some results on compressibility and shear strength. Results of triaxial UU, laboratory vane test, consolidation test and triaxial CIU are presented. Data are also examined with respect to disturbance due sampling and some field and laboratory procedures are proposed.